An Achromatic Focal Plane Mask for High-Performance Broadband Coronagraphy. (4th January 2016) - Newman, K.; Guyon, O.; Balasubramanian, K.; Belikov, R.; Jovanovic, N.; Martinache, F.; Wilson, D.
Abstract: Developments in coronagraph technology are close to achieving the technical requirements necessary to observe the faint signal of an Earth-like exoplanet in monochromatic light. An important remaining technological challenge is to achieve high contrast in broadband light. Coronagraph bandwidth is largely limited by chromaticity of the focal plane mask, which is responsible for blocking the stellar PSF. The size of a stellar PSF scales linearly with wavelength; ideally, the size of the focal plane mask would also scale with wavelength. A conventional hard-edge focal plane mask has a fixed size, normally sized for the longest wavelength in the observational band to avoid starlight leakage. The conventional mask is oversized for shorter wavelengths and blocks useful discovery space. We present a new focal plane mask which operates conceptually as an opaque disk occulter, but uses a phase mask technique to improve performance and solve the "size chromaticity" problem. This achromatic focal plane mask would maximize the potential planet detection space without allowing starlight leakage to degrade the system contrast. Compared with a conventional opaque disk focal plane mask, the achromatic mask allows coronagraph operation over a broader range of wavelengths and allows the detection of exoplanets closer to their host star. We present the generalized design for the achromatic focal plane mask, implementation within the Subaru Coronagraph Extreme Adaptive Optics instrument, and laboratory results which demonstrate the size-scaling property of the mask.